Three communications challenges for social change - Gumucio-Dagrón, Alfonso (2008)
Communication for social change faces three mayor challenges both in the academic environment and in the development field: naming things, develop ing discipline and to legitimize the communication for social change in the big agencies that make important decisions. A greater awareness regarding that programs can only be sustainable if the communities —the “ beneficiaries”— take over them, but this take-over-through-participation-process is only possible in the event that a communication witch strengthen the communities from there voice, identity and culture appears.